STUDY OF THE RHEOLOGICAL PROPERTIES OF DIRECT TYPE COSMETIC EMULSIONS DEVELOPED ON THE BASIS OF THE COMPOSITIONS OF SILICONES - VASYLCHENKO, Iryna; KUPRIY, Yaroslav; SEMESHKO, Olga (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the results of studies of the rheological properties of cosmetic emulsions developed using compositions of silicones in order to obtain systems with optimal thixotropic and extrusion properties.Small-component direct emulsions based on the mineral oil and the compositions of the BRB International BV (Netherlands) brand silicones, that are Silicone Oil 350 cSt – individual silicopolydimethylsiloxane and BRB 1288 – mixed amodimethicone, were used as the objects of the study. The rheological properties of emulsions were determined using a rotational viscometer "Rheotest - 2" by establishing the dependence of the viscosity of emulsions and the applied shear stress on the shear rate. Based on the data obtained, the dynamic viscosity indicators, dynamic fluidity coefficients at various shear rates, as well as the mechanical stability index of the studied systems were calculated.As a result of the rheological studies of the obtained cosmetic emulsions based on the compositions of silicones, the type of their flow and the presence of thixotropic properties were established. The emulsion sample has been determined that has the most pronounced elastic properties and the highest value of the flow limit. The study of the extrusion properties of emulsions by calculating the coefficients of dynamic fluidity made it possible to determine the emulsion sample that has a low dynamic rarefaction and can be characterized by easier distribution over the skin and, at the same time, can easily and freely move through the process equipment. The composition of the emulsion is found, the mechanical stability of which is high, which will contribute to the preservation of its structure in the process of irreversible deformation. The rheological studies have established the composition of the cosmetic emulsion based on the Silicone Oil 350 cSt polydimethylsiloxane and the BRB 1288 amodimethicone, which is characterized by optimal viscosity, rheological and extrusion properties.
Keywords: emulsions; cosmetic silicones; polydimethylsiloxane; amodimethicone; rheology; extrusion properties; mechanical stability